A brief history of Konya - Birekul, Mehmet (Kültür A.Ş, Metropolitan Municipality of Konya, 2005)
The book consists of a brief history of the cultural and historical richness of the city of Konya. Konya, which has been playing a centrel role being a cradle for many civilizations throughout the history, is one of the unique centers that combine its historical heritage and cultural accumulation with present time. The city of Konya is considered the first place of the permanent settlements which became a center for many societies, nations and civilizations from Çatalhüyük to Hitits; from Frigs to Kimmers; from Lidyas to Pers; from Greeks to Great Iskender; from Romans to Selçuks, Ottomans and the period of the Republic of Turkey. It is an ocean that each of the scholars individually like Mawlana Jalaleddins,Shams Tabrizis, Konevis and Nasreddin Hodjas and many others are considered as a river unifies within. Konya is a full of peace city that embeds tolerance seeds wavy into the hearts of the people.